PERSEPSI DAN DAMPAK KEBIJAKAN PEMERINTAH TERHADAP USAHATANI DI WILAYAH PERBATASAN INDONESIA-MALAYSIA KABUPATEN BENGKAYANG - , Yulianus, S.Hut.,M.Si. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This study aims to (1) analyze farmers perception of government programs on the agricultural sector in the border region of Bengkayang Regency (2) Measuring the contribution of farming to the income of farm households in the border region of Bengkayang Regency (3) analyze the factors that influence the choice of output market, productivity levels and farm incomes in the border region of Bengkayang Regency, and (4) analyze the influence of government programs and border markets to the level of productivity, income and relative economic efficiency of farm in the border region of Bengkayang Regency. The research was conducted in the border region of Bengkayang Regency, namelySeluas District and Jagoi Babang District. Respondents of this study amount 200 people that consists of 100 people in Seluas District and 100 people in the Jagoi Babang District. Types of farms analyzed in this study were rubber farming, dry land rice farming, and wet land rice farming. Analysis of data using the method of Miles and Hubermas Triangulation Model, Multinomial Logit Model (MNL), and Ordinary Least Square Model (OLS). The research results showed that: (1) According to the farmers perception, the success rate of Government programs in the agricultural sector in the border region of Bengkayang regency is still low. This is caused by programs are not socialized in optimally, inappropriately planed programs, and lack of supervision on the implementation of Government program